Bioekologi vektor demam berdarah dengue (DBD) serta deteksi virus dengue pada Aedes aegypti (Linnaeus) dan Ae. albopictus (Skuse) (Diptera: Culicidae) di kelurahan endemik DBD Bantarjati, Kota Bogor - Zahara Fadilla; Upik Kesumawati Hadi; Surachmi Setiyaningsih (Jurnal Entomologi Indonesia, 2015)
Dengue hemorrhagic fever (DHF) is a viral disease that threatened community health in Indonesia. As part of an eradication program, it is important to learn the behavioral aspect of the disease vector. The aims of this study were to detect the presence of dengue virus in Aedes spp., at Bantarjati Village, Bogor City and to learn to bioecology of. Aedes aegypti (Linnaeus). Detection of dengue virus in Aedes spp. were done by reverse transcription-polymerase chain reaction (RT-PCR) technique that consist of two phase were synthesis phase and cDNA amplification and dengue virus serotipe characterization. The Ae. aegypti and Ae. albopictus (Skuse) mosquitoes were collected using the landing and resting moquito collection technique booth indoors and outdoors. The highest density of Ae. aegypti and Ae. albopictus were found in April and the peak activity was occurred at 10:00-11:00 am. Dengue virus was not detected in female mosquitoes Aedes spp.